TEACHER’S ATTITUDE TOWARDS CREATIVE TEACHING STRATEGIES FOR ENHANCING STUDENTS’ ACADEMIC ACHIEVEMENT AT HIGHER SECONDARY LEVEL - T., MUTHUKUMAR; K., GUNASEKARAN (International Journal of Psychosocial Rehabilitation, 2020)
In this paper the investigator to explicit the creative teaching strategies for enhancing the students’ academic achievement at the higher secondary level. The Innovativeness is a different reasoning capacity that performs on the familiarity, adaptability, and uniqueness of speculation, affectability to issues, and reclassifies and fines existing thoughts. To find out teacher’s attitudes towards creative teaching strategies for enhancing students’ academic achievement at the higher secondary level. The investigator adopted the Survey method of Research. The investigator is consulted with his guide prepared a questionnaire consisting of 25 questions. To establish the content validity their liability value is 0.69. The population for survey research for the present study constitutes about 145 teachers of both higher secondary schools of Sivaganga District. Adequate creative teaching aids, textbooks, should be provided in every school. Creative, learning activity of teachers will help them to update their knowledge. The findings of the study the Null hypothesis is accepted to the attitude of the urban school teachers and rural school teachers both are not significant.